TINGKAT DIPENDENSI PARADIGMA DOMINANSI SOSIAL PADA JENIS KELAMIN DI AREAL HUTAN LINDUNG MANGUNAN KABUPATEN BANTUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA 2015 - Rosadi Rofik (Program Studi Manajemen Lingkungan, 2017)
The objective of the research is to draw connections and dependencies of Dominant Social Paradigm level on sex in the protected forest Mangunan, Kabupaten Bantul, Yogyakarta in 2015. This quantitative research refers to the condition in the past against environmental degradation in the district of Bantul. Data obtained by participant observation, using a Likert questionnaire, in inputting the interaction of each sex to the environment, based on the analysis unit Dominant Social Paradigm, which consists of three components, namely: socio-economic aspects, Character Dominant (anthropocentrism), and the organism cosmologis. Then, statistical analysis using Chi-square test for independent to stack up against two units of analysis, namely Dominant Social Paradigm and sex. The conclusion of this research is, there is a relationship of the Dominant Social Paradigm with sex either Male or Female in Mangunan Bantul district of Yogyakarta province. Problem solving on lowering the quality of the environment characterized by measurement results of depencies of Dominant Social Paradigm level which performed by each sex as a problem to be solved. Recommendations resolving the issue by implementing a new paradigm of Ecology (New Ecological Paradigm) in an effort Protected Forest Quality Improvement Mangunan